Lietuvių gimininės pravardės - Butkus, Alvydas (Baltistica, 1989)
LITHUANIAN NICKNAMES REFERRED TO A PERSON’S KINSHIP In this paper a synchronical approach of the modern Lithuanian nicknames referred to a person’s kinship or dependence on the particular family is given. There exist about 18.4% of such nicknames. Most of them (93%) are patronymic names. They have a status of nicknames since they are unofficial names and point to a man’s kinship, whereas the other nicknames point to other features. Moreover, they entirely displace a person’s real name and become the only name by which he is known. The patronymic names as nicknames dominate in Dzūkija (Southern Lithuania) and Aukštaitija (Eastern Lithuania). From the structural point of view they are of four different kinds: (a) derivatives (68.8%), e. g. Adomiõkas (: Adomas), Kãsčius (:Kastas, Konstantinas); (b) primary words, i. e. unchanged fathers’ names (24.1%); (c) composites (6.8%): Jõno Pẽtras (Peter of John); (d) compound words (0.6%): Jùrgpetris (Georgepeter, i. e. Peter of George). More frequently the derivatives are produced by suffixation. The suffixes -(‘)ukas and -(‘)okas are used very often. The suffix-(‘)ukas is widespread throughout Lithuania, the -(‘)okas dominates in Aukštaitija. Other suffixes (-ėnas, -elis / -ėlis, -ynas, -utis,-(’) ulis, -iškis, -aitis) are met rather rarely. We have registered 87 suffixes of sons’ nicknames, only 11 suffixes of these, however, are used for the composing of nicknames which number more than 1%. A small part of the nicknames is related with marriage. If one is married into a farm to a daughter or a widow, he receives the nickname pointed to this status. 70% of such nicknames coincide with the wife’s or father-in-law’s name, i. e. with the name of the farm’s master. Wives always have names derived from their husbands’ names, also in the case of a husband married into a farm.